Analisis Pengaruh Current Ratio (Cr) dan Debt To Equity Ratio (Der) Terhadap Return On Asset (Roa) Pada Pt Graha Layar Prima Tbk - Yohanes Sugiyanta; Asrul (Mulia Pratama, 2021)
It is suspected that the Current Ratio (CR) has a partially negative and significant effect on Return on Assets (ROA). Based on the background of the problems in this study, it can be formulated how the influence of Current Ratio (CR) on Return on Assets (ROA) at PT Graha Layar Prima Tbk. And what is the effect of Debt to Equity Ratio (DER) on Return on Assets (ROA) partially at PT Graha Layar Prima Tbk, also how is the effect of Current Ratio (CR) and Debt to Equity Ratio (DER) on Return on Assets (ROA) in general? simultaneously at PT Graha Layar Prima Tbk. This study aims to determine the effect of Current Ratio (CR) and Debt to Equity Ratio (DER) on Return on Assets (ROA). This research is a quantitative data with explanatory research that explains the relationship or influence between variables. From the results of research on PT Graha Layar Prima Tbk, Current Ratio (CR) has a negative and significant effect on Return on Assets (ROA). Meanwhile, the Debt to Equity Ratio (DER) has a negative and significant effect on Return on Assets (ROA) From the results of research on PT Graha Layar Prima Tbk, Current Ratio (CR) has a negative and significant effect on Return on Assets (ROA). Meanwhile, the Debt to Equity Ratio (DER) has a negative and significant effect on Return on Assets (ROA). The benefits of this research are to contribute ideas to the development of economics regarding the effect of Current Ratio (CR) and Debt to Equity Ratio (DER) on Return on Assets (ROA) at PT Graha Layar Prima Tbk and can be used as a basis for research expansion, especially related to financial performance associated with companies that go public in further research.